1992
DOI: 10.1093/jnci/84.22.1736
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition With Reversible Cell Cycle Arrest of Carcinoma Cells by Flavone L86-8275

Abstract: These findings suggest that L86-8275 is a candidate for further preclinical development, as well as a model for the synthesis of other flavonoids that might potently delay cell cycle progression to achieve inhibition of tumor growth. Future studies need to address optimal schedules for antiproliferative activity in vivo and inhibition of clonogenic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(160 citation statements)
references
References 0 publications
5
149
0
4
Order By: Relevance
“…Initial studies revealed that¯avopiridol could induce cell cycle arrest at either G1 or G2/M, concordant with the ability of¯avopiridol to inhibit both cdk2 and cdk1, respectively (Kaur et al, 1992;. To determine the e ects of¯avopiridol on cdks, studies utilizing puri®ed cdk's showed that¯avopiridol inhibits cdks 1, 2, 4 and 6 in a competitive manner with respect to ATP, with a Ki of 41 nM, with somewhat less potent e ect on cdk 7 (cdk-activating kinase) (Carlson et al, 1996a,b;Losiewicz et al, 1994;Singh et al, 1999;Worland et al, 1993).…”
Section: Flavopiridolmentioning
confidence: 78%
“…Initial studies revealed that¯avopiridol could induce cell cycle arrest at either G1 or G2/M, concordant with the ability of¯avopiridol to inhibit both cdk2 and cdk1, respectively (Kaur et al, 1992;. To determine the e ects of¯avopiridol on cdks, studies utilizing puri®ed cdk's showed that¯avopiridol inhibits cdks 1, 2, 4 and 6 in a competitive manner with respect to ATP, with a Ki of 41 nM, with somewhat less potent e ect on cdk 7 (cdk-activating kinase) (Carlson et al, 1996a,b;Losiewicz et al, 1994;Singh et al, 1999;Worland et al, 1993).…”
Section: Flavopiridolmentioning
confidence: 78%
“…It inhibits CDK1, CDK2, CDK4 and CDK7 at IC 50 value range of 0.04-0.4 M (Losiewicz et al 1994;Carlson et al 1996). It was Wrst discovered as epidermal growth factor receptor (EGFR) inhibitor, which inhibits at IC 50 value of 21 M. Later, it was shown that Xavopiridol could inhibit the growth of breast and lung cancer cell lines (Kaur et al 1992) and prostate, head and neck cancer and leukemia xenografts (Drees et al 1997;Patel et al 1998;Arguello et al 1998). Since it did so at much lower concentrations than those needed for the inhibition of the EGFR, new targets were investigated and its eVect on CDKs was found.…”
Section: Broad-range Inhibitorsmentioning
confidence: 99%
“…X-ray crystallography data were collected using an area detector mounted on a D8 platform goniometer using graphite-monochromated Mo Kα radiation (λ= 0.71073Å). The X-ray crystallographic data for compounds 10, and 18b have been deposited with the Cambridge Crystallographic Data Center and have been allocated the deposition numbers CCDC 293761 (10) and CCDC 293762 (18b). Optical rotations were obtained at room temperature.…”
Section: Methodsmentioning
confidence: 99%